Determinants of Participation of Young Farmers with and without Disability in Capacity building Programs Designed for the Public in Uganda - Agole, David; Epeju, William Faustine (Machakos University, 2019)
Participation of young farmers with disabilities in agricultural capacity-building programs in their communities is important as poverty reduction strategy in people with disabilities in Uganda. This research study comparatively examined participation of young farmers with and without disabilities in capacity-building programs designed for the public in Northern and Eastern Uganda. The study employed a comparative, mixed methodology, cross sectional research designs involving 774 young farmers composed of 388 with disabilities and 386 who had no disabilities. The sample selection strategies involved the use of a stratified, and random sampling techniques. This research utilized an interviewer-administered paper survey in collecting data. Descriptive statistics and regression analyses were used in analysing quantitative data. The findings indicate that young farmers with a disability and being contacted face-to-face were less likely to participate in community capacity-building programs. In contrast, Northern Uganda, those contacted in a group setting, application of sign language interpretation, being female, and having supportive training staff increased the chances of their participation in community capacity-building programs
Keywords: Agriculture; Capacity-building programs; Disability; Participation; Youth with and without disability.